2017
DOI: 10.1039/c7cp04540a
|View full text |Cite
|
Sign up to set email alerts
|

Pd-P nanoparticles supported on PxOy-incorporated carbon nanotubes for enhanced methanol oxidation in an alkaline medium

Abstract: Phosphorous oxide (PO)-incorporated carbon nanotubes (PCNTs) and nitric acid treated carbon nanotubes (OCNTs) are first synthesized, then phosphorous modified palladium nanoparticles (Pd-P NPs) supported on PCNTs (Pd-P/PCNTs) and OCNTs (Pd-P/OCNTs) are synthesized and employed as electrocatalysts in a methanol oxidation reaction. Pd-P/PCNTs show enhanced electrocatalytic activity and stability in comparison to Pd-P/OCNTs. Combining surface analysis and electrochemical performance, PO incorporated into CNTs cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…It is well documented that the lower the value of the Tafel slope, the higher will be the electrocatalytic activity. A lower magnitude of Tafel slope also indicates higher tolerance of the active electrocatalyst toward the poisoning species . Results obtained from the Tafel slope indicate that among the three modified electrodes, Ni 0.5 Cu 0.5 Co 2 O 4 (30%)/Ni 2 Cu 1 -MesoZ/GCE has the lowest Tafel slope (Figure ) and therefore exhibits a strong tolerance behavior toward the various intermediate species, which is the prime reason for its higher methanol electro-oxidation ability.…”
Section: Evaluation Of Electrocatalytic Activitymentioning
confidence: 97%
See 1 more Smart Citation
“…It is well documented that the lower the value of the Tafel slope, the higher will be the electrocatalytic activity. A lower magnitude of Tafel slope also indicates higher tolerance of the active electrocatalyst toward the poisoning species . Results obtained from the Tafel slope indicate that among the three modified electrodes, Ni 0.5 Cu 0.5 Co 2 O 4 (30%)/Ni 2 Cu 1 -MesoZ/GCE has the lowest Tafel slope (Figure ) and therefore exhibits a strong tolerance behavior toward the various intermediate species, which is the prime reason for its higher methanol electro-oxidation ability.…”
Section: Evaluation Of Electrocatalytic Activitymentioning
confidence: 97%
“…A lower magnitude of Tafel slope also indicates higher tolerance of the active electrocatalyst toward the poisoning species. 53 Results…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
“…Among them, NaH 2 PO 2 is the most popular by acting as both a reducing agent and a phosphorous source to synthesize PdP x based on the homogeneous precipitation reduction method in aqueous solution or a phosphorization process under high temperature with a N 2 flow. 27,82,[94][95][96] During this process, breaking strong P-O bonds can be facilitated by metal particles which enhance the adsorption of H on metal and spill over from the phosphate, giving rise to the reduction of phosphate to phosphide. 97 Shao and co-workers reported that highly dispersed and ultrafine Pd-P NPs with an fcc structure supported on O-functionalized carbon nanotubes (OCNTs) could be synthesized by the reduction of Pd(II), with NaH 2 PO 2 as a reducing agent and P source in aqueous solution upon heating at 80 °C for 4 h. 95 For the nanomaterial-based catalysts, the morphology has a significant influence on the catalytic performance.…”
Section: Phosphorus Atom-doped Pd Nanomaterialsmentioning
confidence: 99%
“…27,82,[94][95][96] During this process, breaking strong P-O bonds can be facilitated by metal particles which enhance the adsorption of H on metal and spill over from the phosphate, giving rise to the reduction of phosphate to phosphide. 97 Shao and co-workers reported that highly dispersed and ultrafine Pd-P NPs with an fcc structure supported on O-functionalized carbon nanotubes (OCNTs) could be synthesized by the reduction of Pd(II), with NaH 2 PO 2 as a reducing agent and P source in aqueous solution upon heating at 80 °C for 4 h. 95 For the nanomaterial-based catalysts, the morphology has a significant influence on the catalytic performance. In comparison with 0D isotropic NPs, 1D noble metal nanowires (NWs) and 3D nanoparticle networks (NNs) can not only facilitate the electron/mass transfer and magnify the active area accessible to the reactant molecules, but also improve the stability by decreasing the Ostwald ripening and inherent dissolution processes during the electrocatalysis.…”
Section: Phosphorus Atom-doped Pd Nanomaterialsmentioning
confidence: 99%
“…Before the actual performance of the experiments, een successive cycles were run to stabilize the working electrode. 40 The electrochemical performance of methanol oxidation was analyzed by the forward peak current density (I f ), and the backward current density (I b ) and the ratio of the I f and I b that is the maximum current density has been calculated from the CV curve 41 in Fig. 6.…”
Section: Transmission Electron Microscope (Tem)mentioning
confidence: 99%